Kebiasaan Merokok di Kalangan Siswa: Studi Kasus di Tiga SMK di Malang - Mohammad Efendi (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
This study aimed at describing teenagers’ smoking frequency and analyzing the factors which encouraged them to smoke. Data were collected from 120 respondents taken randomly from one public and 2 private vocational schools. The result showed that 59.17% students were active smokers, and 67.87% smoked 1 to 3 cigarettes per day. 47.89% students smoked because of their school mates’ invitation. Other findings showed that smoking was not considered as a dangerous threat for health. These students even thought that smoking could grow courage, help solve problems, increase self confidence, serve as identity for men, and means for building social life.